A self-organised middleware architecture for Wireless Sensor Network management. (21st May 2008) - Yu, Mengjie; Mokhtar, Hala; Merabti, Madjid
In this paper, we propose a lightweight middleware system that supports Wireless Sensor Networks (WSNs) to handle real-time network management using a hierarchical framework. The primary objective of this middleware is to provide standard management services for sensor applications to maintain network service quality with minimal human intervention. Middleware of sensor node also reconfigures its functionality autonomously to reflect changes of node resources expenditure or network environment. In addition, we propose an alternate power management solution to achieve energy efficiency of sensor networks via controlling management performance of sensor nodes. This approach reduces node energy consumption without frequent reconfiguration of network management structure.